Strategies to Deal with Change - Bassendowski, Sandra (Operating Room Nurses Association of Canada Journal, 1998)
My presentation will focus on change and on strategies that can assist us to deal with change. You know all about change and what it is like to experience change day after day and month after month. You have experienced the feelings and emotions related to unending chaos.